The degree of compatibility between the statistical significance and the practical significance indicators in the statistical tests in the master's theses at Omani Universities = درجة التوافق بين الدلالة الإحصائية ومؤشرات الدلالة العملية في الاختبارات الإحصائية برسائل الماجستير بالجامعات العمانية - Al-wahaibi, Salim Khloof; Al-Hidabi, Dawood Abdulmalek Yahya; Ali Al-Khrosi, Huseen (The Scientific Institute For Advanced Training and Studies, 2020)
هدفت الدراسة إلى بحث درجة التوافق بين الدلالة الإحصائية والدلالة العملية في رسائل الماجستير التربوية بالجامعات العمانية (جامعة السلطان قابوس، وجامعة نزوى، وجامعة ظفار، وجامعة صحار)، منذ بداية تطبيق برامج الماجستير فيها وحتى نهاية عام 2018 م، وبلغ مجتمع الدراسة ( 1895 ) رسالة ماجستير، وتم اختيار( 33.14 %) كعينة للدراسة، وبلغ عددها ( 628 ) رسالة ماجستير، من جميع الجامعات، وقام الباحث بتصميم أداة؛ لجمع البيانات الخاصة بالاختبارات الإحصائية التي تضمنتها هذه الدراسة، وهي اختبارات (ت) بأنواعها الثلاثة، واختبارات التباين بأنواعها الثلاثة، ومعامل ارتباط بيرسون، ومعامل الانحدار. توصلت النتائج إلى وجود علاقة إيجابية ذات دلالة إحصائية، بين الدلالة الإحصائية وكل من مستويات الدلالة العملية، في جميع الاختبارات الإحصائية، فأغلب النتائج الدالة إحصائيا اقترنت بدلالة عملية متوسطة أو كبيرة، كما أن أكثر النتائج غير الدالة إحصائيا اقترنت بدلالة عملية صغيرة، كذلك أشارت النتائج إلى أن ( 26.5 %) من القرارات التي توصلت إليها نتائج رسائل الماجستير بالجامعات العمانية قد تكون غير دقيقة، ولايمكن الاعتماد عليها، كما أن أغلب الدراسات التي بحثت العلاقة بين المتغيرات في الجامعات العمانية قد وقعت في الخطأ من النوع الأول ( α) وهو رفض الفرضية الصفرية وهي في الواقع صحيحة، ودلت النتائج على وجود ضعف في التصميم المستخدم لحساب معاملات الانحدار في رسائل الماجستير بجامعة السلطان قابوس وجامعة نزوى. ****************************************************************************** The present study aimed to investigate the degree of compatibility between statistical significance and practical significance in educational master’s theses in Omani universities (Sultan Qaboos University, University of Nizwa, Dhofar University and Sohar University), during 1998-2018.The total population (1895) and a random sample of (628) master's Theses was selected, which is (33.14%) from all universities, and the researcher designed a tool to collect data for the statistical tests that were included in this study, which are t tests, analysis of variance tests, Pearson correlation coefficient and regression coefficient. The results concluded that there is a positive statistically significant relationship between the statistical significance the levels of practical significance, in all statistical tests. Also (26.5%) of the master’s theses decisions at Omani universities may be inaccurate and unreliable. The results of the study showed that the most Master's Thesis that examined the relationship between the variables at Omani universities have occurred in the first type of error (α), and the results indicated a weakness in the design used to calculate regression coefficients in master's theses at Sultan Qaboos University and Nizwa University.